Behavioural responses of songbirds to preen oil odour cues of sex and species. (October 2019) - Grieves, Leanne A.; Bernards, Mark A.; MacDougall-Shackleton, Elizabeth A.
Abstract : Chemical signalling is widespread across animal taxa. Even birds, once thought to have little or no sense of smell, are now known to possess a fully functional olfactory system and may thus respond to conspecific and heterospecific chemical signals. In birds, body odour derives primarily from preen oil, a complex chemical mixture that is potentially rich in information: for example, preen oil chemical composition differs between the sexes and among species. Hypothesizing that songbirds attend to preen oil odour cues in the contexts of intra- and interspecific communication, we presented breeding-condition adult song sparrows, Melospiza melodia, with preen oil odour cues in two-choice tests. We compared time spent in a Y-maze arm scented with preen oil from same-sex conspecifics relative to the absence of such odour; from opposite-sex relative to same-sex conspecifics; and from female brown-headed cowbirds, Molothrus ater (frequent brood parasites of song sparrows), relative to the absence of such odour. The time spent with same-sex conspecific preen oil was not significantly different than time spent without odour. However, both males and females spent more time with opposite-sex than same-sex preen oil. We found a sex-by-stimulus interaction with respect to female cowbird odour: male song sparrows spent more time with cowbird preen oil than without odour, but female song sparrows showed the opposite pattern. Our findings show that even relatively nonsocial species can attend to the information contained in preen oil secretions. Highlights: Songbird preen oil chemical composition differs between species and sexes. Song sparrows spent more time with opposite-sex than same-sex conspecific odour. Males spent more time with female cowbird odour while females did the opposite. Even relatively nonsocial species attend to information in preen oil secretions.